1988
DOI: 10.1093/infdis/158.1.132
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of Healthy Adults with Live Attenuated Varicella Vaccine

Abstract: Live attenuated varicella vaccine was administered to healthy varicella-susceptible adults. Of 187 adults immunized with the Oka strain of vaccine, seroconversion to varicella-zoster virus (VZV) occurred in 82% after one dose and in 94% after two doses. Adverse effects were unusual. After immunization, one subject developed mild zoster caused by wild-type virus. Twelve adults developed a mild breakthrough case of chickenpox after exposure to VZV. Protection after household exposure was observed in nine (56%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
0
3

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(63 citation statements)
references
References 16 publications
4
56
0
3
Order By: Relevance
“…42,59,60 No published data are available on the proportion of adolescents or adults who achieve a gpELISA concentration of Ն5 U/mL after either 1 or 2 doses of varicella vaccine. Persistence of antibody over the ensuing decade in this population varies, but studies using the FAMA assay have suggested that approximately 30% of adults lose detectable antibodies over this time period.…”
Section: Immunogenicitymentioning
confidence: 99%
“…42,59,60 No published data are available on the proportion of adolescents or adults who achieve a gpELISA concentration of Ն5 U/mL after either 1 or 2 doses of varicella vaccine. Persistence of antibody over the ensuing decade in this population varies, but studies using the FAMA assay have suggested that approximately 30% of adults lose detectable antibodies over this time period.…”
Section: Immunogenicitymentioning
confidence: 99%
“…It is highly sensitive because the preservation of the structure of the surface glycoproteins on infected cells allows neutralising antibodies to be detected [389] . It has been used to assess protection against varicella as a value of ≥ 4 correlates with protection [215,347,376,[390][391][392] . Its limitations are that it is semi-quantitative, cannot be automated, and requires specialised personnel and specific equipment; reading is subjective and subject to inter-laboratory variability [30] .…”
Section: Ifamentioning
confidence: 99%
“…The development by Takahashi and his colleagues of the live attenuated Oka strain of VZV in the early 1970s made it possible to immunize VZV-naive children and adults against varicella [33][34][35][36] and to explore the possibility of boosting VZV-CMI in older adults [21,31]. Subsequent studies have demonstrated that Oka-derived VZV vaccines can elicit a significant increase in VZV-CMI in immunocompetent older adults [32,[37][38][39] and can reduce the incidence and severity of HZ in recipients of bone marrow allografts [40,41].…”
mentioning
confidence: 99%